Kontekstualisasi Miskomunikasi dalam Al-Qur’an (Studi atas Tafsir Al-Qur’an Tematik Lajnah Pentashihan Mushaf Al-Qur’an Kementerian Agama RI) - Ulvah Nur’aeni (Nun : Jurnal Studi Alquran dan Tafsir di Nusantara, 2021)
This paper answers two main questions. First, how is the methodology used by Tafsir Al-Qur’an Tematik of the Ministry of Religion of RI to produce interpretations that can offer solutions to the problems of Umma? Second, what is the contextual interpretation of the current miscommunication?. These Questions arise because the various methods of interpretation that exist often indicate a large distance between the Qur’an and the problems of Umma. Al-Qur’an as a book of guidance is deemed not present to answer the challenges that come so that it becomes a book that does not show its relevance in every time and place as well as the development of mankind. Especially the problems of miscommunication that come along with technological sophistication and increase the interest of the Indonesian people towards social media. Cyberbullying, dispute of religious authority, plagiarism, massive provocation, and other problems arise because of miscommunication. Therefore, a solution is needed that can answer these problems through the signals contained in the Al-Qur’an. One of the tafsir that offers such a solution is Tafsir Al-Qur’an Tematik compiled by the LajnahPentashhihMushaf Al-Qur’an of the Ministry of Religion of the Republic of Indonesia with the theme “KomunikasidanInformasi”. This article examines this interpretation using descriptive analysis methods.